2023
DOI: 10.1136/wjps-2022-000513
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psychosocial interventions for pediatric patients with scoliosis: a systematic review

Abstract: BackgroundPediatric patients affected by scoliosis have complex psychological and social care needs, and may benefit from psychosocial interventions. We therefore aimed to summarize evidence of the efficacy of psychosocial interventions for this patient population.MethodsLiterature was identified by searching Medline, PsycINFO, Embase, EBSCO Cumulated Index to Nursing and Allied Health Literature (CINAHL), and Cochrane Central Register of Controlled Trials (CENTRAL) from database inception to 20 March 2022. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…Considering psychological interventions for patients undergoing spinal surgery, a systematic review performed by van Nekierk et al [53] revealed six studies focused on patients with AIS undergoing spinal surgery [52][53][54][55][56][57][58][59]. Most of them were randomized clinical trials (RCTs) [55][56][57][58][59][60][61] and excluded patients with psychological, cognitive, and/or developmental conditions [54][55][56][57][58]60,61].…”
Section: The Significance Of Cbt Intervention In Ais Patients (Cross-...mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering psychological interventions for patients undergoing spinal surgery, a systematic review performed by van Nekierk et al [53] revealed six studies focused on patients with AIS undergoing spinal surgery [52][53][54][55][56][57][58][59]. Most of them were randomized clinical trials (RCTs) [55][56][57][58][59][60][61] and excluded patients with psychological, cognitive, and/or developmental conditions [54][55][56][57][58]60,61].…”
Section: The Significance Of Cbt Intervention In Ais Patients (Cross-...mentioning
confidence: 99%
“…The first kind of interventions incorporated components such as guided imagery and relaxation training [53][54][55][56][57], specific medical information teaching [56][57][58]60] and music therapy [59]. In general, most studies did not report convincing evidence of brief educational interventions being more efficacious than routine medical care in improving outcomes.…”
Section: The Significance Of Cbt Intervention In Ais Patients (Cross-...mentioning
confidence: 99%
See 1 more Smart Citation